Electrochlorination method for iron collector recycling. (2020) - Antonov, Andrey; Tietz, Andreas; Kirichenko, Andrey; Polyakov, Nikolay; Ehrenburg, Maria; Botryakova, Inna
Abstract: Practical methods of recycling spent automotive catalysts and their main disadvantages in industrial using are described. The hydrometallurgy method with electrochlorination is proposed as the basis of the platinum-group metals extraction technology after electric arc melting of ceramic catalysts carrier material with iron collector. The recovery of Platinum metals group materials from spent automotive catalysts was examined. Data obtained of the platinum, palladium, rhodium extraction are analyzed.